2009
DOI: 10.1097/brs.0b013e3181b353ea
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Segmental Mobility According to the Grade of the Disc, the Facet Joint, the Muscle, and the Ligament Pathology by Using Kinetic Magnetic Resonance Imaging

Abstract: Our results support that facet joint degeneration is followed by disc degeneration according to age. Increased translational movements of the lumbar segments occurred in severe disc degeneration accompanied by facet joint degeneration or the presence of LFH even if the movements were stabilized in the advanced status. Therefore, the current status of the intervertebral discs, facet joints, and ligamentum flavum should be taken into consideration when evaluating stability within the lumbar spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
66
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 32 publications
8
66
0
Order By: Relevance
“…This effect was found to be significantly correlated with all scores, and is coherent with previous in vivo and in vitro data for high degrees of disc degeneration [20,40,49]. However, for mild degeneration instability was found in two studies [20,40], while stiffening was observed in the other one [49]. The present work supported the findings of the latter.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This effect was found to be significantly correlated with all scores, and is coherent with previous in vivo and in vitro data for high degrees of disc degeneration [20,40,49]. However, for mild degeneration instability was found in two studies [20,40], while stiffening was observed in the other one [49]. The present work supported the findings of the latter.…”
Section: Discussionsupporting
confidence: 93%
“…This idea, supported by more recent studies [20,40] had a critical influence on the development of the therapeutic options, e.g. for dynamic stabilization, which is aimed to the reduction of the flexibility to physiological levels.…”
Section: Introductionmentioning
confidence: 91%
“…Karadimas et al [17] studied healthy and degenerative discs using positional MR images and found that changes in segmental motion were related to the degree of disc degeneration. Using kMRI, Kong et al [9,10] found that the prevalence of excessive translational motion significantly increased in patients with grade IV discs, but decreased when the disc degeneration advanced to grade V. Angular motion was similar regardless of disc grade, except in grade V degeneration in which angular motion decreased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we have not taken into account the other factors that may affect segmental mobility, such as degenerative changes of the facet joint, ligamentum flavum, and paraspinal muscles. These structures also play an important role in determining abnormal segmental mobility individually or in combination with disc degeneration [3,10]. Despite these limitations, this study evaluates lumbar segmental mobility in a large population of young patients with a safe and practical imaging technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation